Airway Symptoms and Biological Markers in Nasal Lavage Fluid in Subjects Exposed to Metalworking Fluids - Fornander, Louise; Graff, Pål; Wåhlén, Karin; Ydreborg, Kjell; Flodin, Ulf; Leanderson, Per; Lindahl, Mats; Ghafouri, Bijar (PloS one, 2013)
Occurrence of airway irritation among industrial metal workers was investigated. The aims were to study the association between exposures from water-based metal working fluids (MWF) and the health outcome among the personnel, to assess potential effects on the proteome in nasal mucous membranes, and evaluate preventive actions. The prevalence of airway symptoms related to work were examined among 271 metalworkers exposed to MWF and 24 metal workers not exposed to MWF at the same factory. At the same time, air levels of potentially harmful substances (oil mist, morpholine, monoethanolamine, formaldehyde) generated from MWF was measured. Nasal lavage fluid was collected from 13 workers and 15 controls and protein profiles were determined by a proteomic approach. Airway symptoms were reported in 39% of the workers exposed to MWF although the measured levels of MWF substances in the work place air were low. Highest prevalence was found among workers handling the MWF machines but also those working in the same hall were affected. Improvement of the ventilation to reduce MWF exposure lowered the prevalence of airway problems. Protein profiling showed significantly higher levels of S100-A9 and lower levels of SPLUNC1, cystatin SN, Ig J and β2-microglobulin among workers with airway symptoms. This study confirms that upper airway symptoms among metal workers are a common problem and despite low levels of MWF-generated substances, effects on airway immune proteins are found. Further studies to clarify the role of specific MWF components in connection to airway inflammation and the identified biological markers are warranted.